MODEL BISNIS PENYIARAN DI INDONESIA DALAM EKOSISTEM DIGITAL - Siti Hamidah (Juremi: Jurnal Riset Ekonomi, 2025)
Digitalization is considered a necessity in Indonesia considering the lower class society who have difficulty in knowing this policy or remote areas that are not yet adequate in terms of digital signals. However, digital broadcasting must be done to replace analog. Analog cannot continue to be used because every year the number of broadcast channels will continue to increase while the frequency is limited. This study aims to describe a comprehensive new business model and the relationship between each element in the current digital migration through an analysis of the application of media multiplexing and the development of business models in Indonesia. This study uses a descriptive qualitative method. The results of this qualitative method will produce narratives, not numbers, which from the data obtained will be explained again so that they are in accordance with the research topic. The results of this study are that the preparation of a new business model considers aspects of technology, technology standardization, audience accessibility, business growth, and its implications in society. The conclusion of this study states that the broadcasting business model in Indonesia has many types and categories ranging from local, private, community, and other categories.